Chloroquine or pyrimethamine in salt as a suppressive against sporozoite-induced vivax malaria (Chesson strain) - Coatney, G. Robert (1958)
The authors present the results of a study carried out to determine the efficacy of chloroquine- and pyrimethamine-salt mixtures as a suppressive against sporozoite-induced vivax malaria (Chesson strain). The test subjects used in this study were volunteers of military age in the US Penitentiary at Atlanta, Ga. The subjects chosen were all in good physical condition and had no previous history of malaria. Both drug-salt mixtures were entirely acceptable to the volunteers, were indistinguishable in taste and appearance from ordinary salt, and remained stable under the conditions of food preparation. The weekly dosage of the drugs (300 mg of chloroquine base or 25 mg of pyrimethamine per 50 g of salt) had in each case been adjusted to the average salt consumption. Suppression of malaria was found to be complete throughout the salt-drug regimen and for 28-43 days thereafter, even though the subjects were exposed to repeated heavy doses of sporozoites. In contrast, the control subjects, exposed to the same infective doses, all exhibited parasitaemia 13-15 days after exposure. The procedures for preparing the drug-salt mixtures are described in detail and a simple method for determining the salt consumption by measurement of the urinary chloride excretion is outlined.